THE EFFECT OF SELF EFFICACY ON SCIENTIFIC LITERACY: A CORRELATION STUDY IN ELEMENTARY SCHOOL STUDENTS - Triman Juniarso; Ida Sulistyawati (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2022)
Future generations need scientific literacy to face challenges. One of the factors that influence students' scientific literacy is self-efficacy. The purpose of this study was to analyze how much influence self-efficacy and scientific literacy had. This research is a quantitative correlational study. The population of this research is the population of all fifth-grade students of SDN Kepuh Sedan Sidoarjo. A sample of VA class students was determined through the proportional cluster random sampling technique. The research instrument was a scientific literacy test and a self-efficacy questionnaire developed in a standardized manner. Analysis with simple linear regression test. The study results indicate that: (1) there is a positive influence between self-efficacy on the scientific literacy of elementary school students; (2) The effect of self-efficacy on elementary school students' scientific literacy is 26.2%. This means that 26.2% of the contribution in elementary school students' scientific literacy is influenced by self-efficacy.